Pembuatan Biodisel dari Minyak Jarak dengan Metode TransesterifikasI Menggunakan Etanol Teknis dan Metanol PA - Saripah sobah; Muhammad Naufal Ariq H; Siahaan Theresia (Jurnal Teknik Juara Aktif Global Optimis, 2021)
Increased fuel use can lead to air pollution and other environmental impacts. Substitution of fuel Oil with environmentally friendly fuel alternatives is one solution. Castor oil (Jatropha curcas L) contained in castor seeds can be processed into biodiesel with transesterification process. The most widely used alcohol in the manufacture of biodiesel is methanol. Methanol is made from a material that is not renewable. While ethanol from renewable materials and pure ethanol are expensive. In this study used campurn ethanol to reduce the use of methanol. The purpose of this study is to find out the optimum comparison of methanol-ethanol. The manufacture of biodicells is carried out by a 2-stage process, namely the esterification process and the transesterification process. The esterification process uses HCL catalysts. The transesterification process uses a comparison of methanol and ethanol with variations of 3:1,2:1,1:1,1:2 and 1:3. The catalyst used in the transesterification process is KOH 0.1%. The results showed that the optimum condition in the use of methanol: Technical Etahol is 2:1 within 30 minutes, yielding a yield of 56.1%. The quality test score of type weight and viscosity shows a value of 0.86-0.89 g/mL and 2.9-3.5 so that the results of the study are declared to pass the product test with density and viscosity test standards